Commodification of checks at Chequeado and Lupa branches in Latin America - Alencar, Marta Thaís (2022)
This article discusses the strategies and businesses of the two main fact-checking agencies in Latin America: Lupa (Brazil) and Chequeado (Argentina). Starting from a comparative study of the agencies, the work consists of verifying the commodification of checking for journalism companies and other organizations. Based on the results, the article reveals that fact-checking in Latin America is a business model adopted by the initiatives, which promotes journalistic entrepreneurship and acts, at the same time, in the fight against disinformation and in the defense of democracy.